Microencapsulation as a tool to counteract the typical low bioavailability of polyphenols in the management of diabetes. (May 2020) - Annunziata, G.; Jiménez-García, M.; Capó, X.; Moranta, D.; Arnone, A.; Tenore, G.C.; Sureda, A.; Tejada, S.
Abstract: Polyphenols are secondary metabolites widely distributed in many plant foods, such a tea, coffee, chocolate and fruits. The consumption of these compounds is related to the improvement or amelioration of many diseases, including diabetes. Nevertheless, the great barrier to the therapeutic use of polyphenols is the low bioavailability of these compounds once ingested. For that reason, the encapsulation of polyphenols in different matrices may protect them from digestion and improve their release and subsequent absorption to obtain target-specific health effects. Some studies have reported the beneficial effect of encapsulation to increase both bioavailability and bioaccessibility. However, these works have mostly been carried out in vitro and few studies are specifically addressed at improving diabetes. In the current work, an overview of the knowledge related to nanoparticles and their use in the diabetic condition has been reviewed. Highlights: Polyphenols are a potential tool to ameliorate diabetic disorders. Polyphenols have low bioavailability in humans, limiting their therapeutic effects. Nanoencapsulation increases bioaccessibility and in turn the effects of polyphenols. Clinical trials are necessary to increase the knowledge about nanoencapsulation.